Pelatihan Publikasi Artikel Ilmiah untuk Komunitas Guru Penggerak Kabupaten Polewali Mandar - Nurul Hidayah; Phika ainnadya hasan; Alexander Kurniawan Sariyanto; Meili Yanti; Haryanti Putri Rizal (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Publication of scientific articles is needed by teachers to improve and develop competence and quality of learning. This community service activity aims to provide training to guru penggerak community on how to write scientific articles and introduce scientific journals. The results show that this activity is in demand and provides benefits to guru penggerak community. It can be seen that 69.09% of participants strongly agree that this activity is important to do.